Philosophy 167: Class 7 - Part 8 - Galileo's Tables: Symmetry about 45 Degrees, and the Testability of the Theory. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Description of Galileo's theoretical ballistic tables in the absence of air resistance, and the interesting fact that they are symmetric around a 45 degree angle.; Opening line: "So this is the comment, and now we see what Sagretto says about it."; Duration: 10:48 minutes.; Segment: Class 7, Part 8.